21st‐Century Northeast Asian Order and America's Choice1. (8th August 2016) - Kim, Euikon
Abstract : The emerging new order in Northeast Asia in the 21st century is attributable to a few factors. First, the relative decline of the United States as the hegemonic power contributes to it. Second, the rise of China is also responsible. Buttressed by remarkable economic growth over the past 20 plus years, China is eager to regain its traditional influence and status as the regional hegemon. Third, the relative decline of Japan leads to Northeast Asian power restructuring. Fourth, North Korea is another major factor leading to instability in Northeast Asia. Finally, the rise of South Korea is also responsible for Northeast Asian power restructuring. In the intermediate and long‐run, the US policy toward Northeast Asia will be centered on China, and its China policy will be characterized by engagement and/or hard balancing. To pursue the goal, the United States should further develop close ties with its allies, such as South Korea and Japan, and pursue improved relations with Vietnam and the Philippines. At the same time, the United States should persuade China that cooperating with its neighboring countries would be in its intermediate and long‐term interests. In other words, the United States should firmly and persistently pursue the policy of the "Asianization of China."